(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to problems of forecasting of the ethnic population structure. Methodic of construction of the ethnic forecast is presented, on the basis of the analysis of ethnodemographic development in Ukraine hypotheses of ethnic differentiation of natality, mortality and population migration on prospect are developed. The prognosis of 18 greatest ethnic groups of the ethnic population in Ukraine till 2026 is calculated.